Focusing partnerships : a sourcebook for municipal capacity building in public-private partnerships - Plummer, Janelle (Municipal capacity building series., 2002)
Despite the increasing occurrence of policies aimed at mobilising the financial and human resources of the private sector most urban local governments responsible for urban basic services in the South do not have the capacity to initiate and sustain partnerships. Nor do they understand how they can create partnerships that target the poor. This sourcebook provides practical information and guidance to do so. With extensive illustrative material from Africa Asia and Latin America it sets out a strategic framework for building municipal capacity to create pro-poor partnerships. It focuses on imp.